Physics of atoms and molecules - Chandra, Suresh (New Delhi: Narosa Publishing House, 2010)
This book discusses about the Models for Atoms, One, Two and Several Valence Electron Atoms, Zeeman and Paschen-Back Effects in One and Two Valence Electron Atoms, Stark Effect, X-ray Spectra, Hyperfine Structure, Breath of Spectral Lines, Rotational Spectroscopy, Infrared Spectroscopy and Electronic Structure of Diatomic Molecules. For these topics, every part is explained with the help of simple exercises and by using simple language.
Includes appendices, Bibliography and index
Keywords: Atomic physics -- Molecular physics -- Quantum theory -- Spectroscopy